160 Implementation of serious illness care programme uk for patients with advanced cancer: feasibility study. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - McGlinchey, Tamsin; Mason, Stephen; Coackley, Alison; Roberts, Anita; Maguire, Maria; Sanders, Justin; Maloney, Francine; Block, Susan; Ellershaw, John; Kirkbride, Peter
Abstract : The Serious Illness Care Programme is a complex intervention developed in the US to improve communication between clinicians and patients with serious illness. In collaboration with Aridane Labs the programme has been developed for use within the UK, with pilot implementation funded by NHS England. Within the programme, clinicians are trained in use of a Serious Illness Conversation Guide (the guide), to structure conversations with patients/families. A feasibility of the UK programme is underway, within one North West cancer centre. Aim: To present interim results from the feasibility study Methods: Data on the use and experience of the UK programme, from the perspective of clinicians and patients Quantitative Data: Questionnaires: Clinicians – pre/post training: confidence; attitudes to care of the dying; acceptability of serious illness care programme Patients – pre/post serious illness conversation: Quality of clinical communication; Quality of life; Anxiety; depression. Qualitative Data: In depth interviews: Clinicians: experience of the UK programme, education and training and engaging patients in serious illness conversations Patients: experience of engaging in serious illness conversations, including their acceptability of the approach Results: Quantitative Data: Results will be presented to assess the feasibility and acceptability of the UK programme: Proportion of patients identified conversations and participation in study measures Illustrate any indicative improvements in communication and patient outcomes. Qualitative Data: Thematic Analysis to explore perceptions and experience of the programme: results will highlight main themes, such as: Conversation Value; Holistic and Compassionate; Opening up conversations with family members; Breaking the ice; Timing of conversation and Prognosis. Conclusion: Results from this study suggest these conversations promote shared decision making and individualised care planning, and espouse 'holistic' and 'person centred' care. Further research and evaluation is required to understand the effect of the UK programme on patient outcomes.